Size Effect of Gold Nanoparticles on Optical and Electrical Properties of Au@TiO\(_2\) Nanocomposite Thin Films - Pham, Long Duy; Le, Chi Ha; Nguyen, Oanh Thi Tu; Dang, Chien Tran; Ly, Tai Ngoc; Nguyen, Ngan Thi Thanh; Nguyen Van, Dai; Thach, Lien Thi Dao; Nguyen, Hieu Si (Communications in Physics, 2021)
This study focuses on the influence of gold nanoparticle sizes on optical and electrical properties of Au@TiO2 nanocomposite films. Here, the gold nanoparticles (AuNPs) of different sizes of 5 nm, 10 nm, 20 nm, 40 nm and 60 nm were dispersed onto nanoporous TiO2 thin films to form Au@TiO2 nanocomposite films. FE-SEM images and UV-vis absorption spectra show that AuNPs had good dispersion on the TiO2 films and all Au@TiO2 nanocomposite films exhibited a good surface plasmon resonance (SPR) with the resonance absorption peaks in the visible light region (about 550 nm). The effect of AuNPs on the films photoluminescence property was investigated using excited laser light of 325 nm wavelength at room temperature. The films electrical properties were studied from the change of the photocurrent under illumination of solar simulator and UV light source. The results show that the presence of gold nanoparticles has significantly improved the photocurrent of Au@TiO2 nanocomposite films and especially when AuNPs size was less than 20 nm. In addition, we also found that the photocurrent magnitude of the films with small AuNPs sizes (5 nm and 10 nm) under solar simulator light was 4 times larger than the one under UV light. These results indicate that AuNPs size had a great influence on the improvement of photocurrent in nanocomposite films